Carbon paper for gas diffusion layer of fuel cell and preparation method of carbon paper
By using Pickring emulsion adhesive in the fuel cell gas diffusion layer to bond carbon fibers with iron tetraoxide/carbon nanotube composite particles in the in-situ, the problems of low conductivity and mechanical properties of carbon paper are solved, and high conductivity is achieved The preparation of carbon paper with low cost avoids cracks caused by multiple impregnation of resin and reduced strength at high temperatures.
Patent Information
- Application Number
- CN202411309406.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The existing carbon paper for gas diffusion layers of fuel cells is prone to cracks during the process of impregnating resins for multiple times, with low conductivity and mechanical properties, and high energy consumption and high cost of the preparation method.
The carbon fiber and iron tetraoxide/carbon nanotube composite particles are bonded to the carbon fiber in situ through an alternating magnetic field, avoiding multiple impregnation of resin, and directly through hot pressing to form high conductivity. Low cost carbon paper.
The conductive and mechanical properties of carbon paper are improved, energy consumption and cost are reduced, the problem of reducing mechanical strength of carbon paper at high temperatures is avoided, and high porosity is achieved.
Smart Images

Figure CN119221325A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a carbon paper for a gas diffusion layer of a fuel cell with high conductivity and a preparation method thereof. Background Art
[0002] A fuel cell is an energy conversion device that directly converts the chemical energy of fuel and oxidant into electrical energy. It is not affected by the Carnot cycle, has high conversion efficiency, is highly efficient, clean (the only reaction product is water), and has low noise. Its components mainly include: bipolar plates, gas diffusion layers, catalyst layers, and proton exchange membranes. Among them, the gas diffusion layer (GDL) in the proton exchange membrane fuel cell provides a gas diffusion channel, a supporting material, and improves the performance of the fuel cell.
[0003] GDL is usually composed of porous base layer (MPS) and microporous layer (MPL). MPS is generally made of carbon fiber paper, carbon fiber woven cloth, non-woven fabric and carbon black paper. Carbon fiber paper is widely used due to its corrosion resistance, high conductivity, good air permeability, high strength and smooth surface.
[0004] The typical manufacturing process of carbon fiber paper includes three main steps: wet laying, carbonization and graphitization. In the wet laying process, carbon fibers (usually polyacrylonitrile PAN-based carbon fibers) are impregnated with a carbonizable resin, which acts as a binder for the fibers, and a paper machine is used to form a thin layer of impregnated carbon fibers. The material is then hot-pressed to fuse the carbon fibers and cure the resin; subsequently, carbonization and graphitization are performed.
[0005] Invention patent CN117886298A prepares PAN-based pre-oxidized fibers into non-woven fabrics, impregnates them with phenolic resin and performs molding and curing, performs low-temperature carbonization for the first time, then impregnates them with phenolic resin for the second time and cures, then performs high-temperature carbonization, and finally performs graphitization.
[0006] Invention patent CN117904900A loads a thermosetting resin on a deposited carbon paper obtained by vapor deposition of a carbon paper precursor, and sequentially performs low-temperature pre-curing, hot pressing and carbonization treatment to obtain a densified carbon paper; the densified carbon paper is impregnated in a thermosetting resin ethanol solution, and sequentially performs low-temperature pre-curing, hot pressing and carbonization treatment; the impregnation treatment steps are repeated more than once, and then graphitization is performed to obtain carbon paper for fuel cells.
[0007] With regard to the existing related technologies, there are problems such as cracks in the carbon paper due to multiple impregnations with resin, low electrical conductivity and mechanical properties of the carbon paper, and high energy consumption and cost of the preparation method. Summary of the invention
[0008] The purpose of the present invention is to solve the related problems existing in the background technology part, and to provide a carbon paper for a fuel cell gas diffusion layer and a preparation method thereof, which can improve the electrical conductivity and mechanical properties of the carbon paper and save costs.
[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0010] A method for preparing carbon paper for a fuel cell gas diffusion layer, the method comprising:
[0011] (1) oxidizing carbon nanotubes under strong acid and ultrasonic conditions to introduce carboxyl groups on the surface of carbon nanotubes to obtain carboxylated carbon nanotubes;
[0012] (2) mixing the carboxylated carbon nanotubes with a soluble salt solution containing divalent iron and trivalent iron, adding a small amount of sodium hydroxide solution, and preparing a ferroferric oxide / carbon nanotube composite by a coprecipitation method;
[0013] (3) preparing a Pickring emulsion adhesive by mixing 5-20 wt % of a ferrosoferric oxide / carbon nanotube composite, 5-10 wt % of an adhesive, 0.5-2 wt % of a resin diluent and 70-85 wt % of distilled water;
[0014] (4) dispersing carbon fiber in an aqueous solution containing a dispersant and a surfactant, preparing carbon fiber slurry by beating, and making paper with a papermaking forming paper machine to obtain carbon fiber base paper; wherein the dispersant is 0.10wt%-0.25wt%, the surfactant is 0.01-0.03wt%, the carbon fiber is 0.05-0.1wt%, and the distilled water is 99.62wt%-99.77wt%;
[0015] (5) immersing the carbon fiber base paper in a Pickring emulsion adhesive, and in-situ demulsifying the emulsion particles by an alternating magnetic field, so that the adhesive / ferroferric oxide / carbon nanotube composite particles are precipitated and adsorbed at the fiber overlap points by capillary action, thereby obtaining a carbon fiber bonding base paper;
[0016] (6) The three steps of dewatering the carbon fiber bonding base paper, controlling the orientation of the magnetic conductive particles by a magnetic field, and hot pressing are sequentially performed to obtain a carbon paper for a fuel cell gas diffusion layer having high bonding strength, excellent conductivity, and low cost.
[0017] Furthermore, in step (1), the strong acid is one or more of concentrated sulfuric acid, concentrated hydrochloric acid or concentrated nitric acid, the oxidation temperature is 50-100° C., and the time is 3-8 h.
[0018] Furthermore, in step (2), the divalent iron is ferrous sulfate or ferrous chloride, and the trivalent iron is ferric nitrate or ferric chloride; the concentration ratio of the divalent iron to the trivalent iron is 1:1.75, and the dosage ratio is 1:1.
[0019] Furthermore, in step (2), the heating temperature of the coprecipitation method is 30-80°C and the time is 2-6h.
[0020] Furthermore, in step (3), the adhesive is one or more of phenolic resin, epoxy resin (TDE-85), epoxy resin (E51); and the resin diluent is one of n-hexane, triethylenetetramine or polyetheramine.
[0021] Furthermore, in step (4), the length of the carbon fiber is one or more of 1-9 mm; the mass fraction of the carbon fiber in the carbon fiber slurry is 0.01wt%-0.1wt%
[0022] Furthermore, in step (4), the carbon fiber is one or more of polyacrylonitrile (PAN)-based carbon fiber or asphalt-based carbon fiber; the surfactant is one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate or Tween-80; the dispersant is one or more of polyethylene oxide (PEO), polyacrylamide (PAM), hydroxymethyl cellulose (CMC), and sodium hexametaphosphate.
[0023] Furthermore, in step (6), the hot pressing treatment temperature is 80-180°C, the pressure is 2.5-10Mpa, and the time is 30-120min.
[0024] A carbon paper for a fuel cell gas diffusion layer prepared by the above preparation method.
[0025] The beneficial effects of this application compared to the prior art are:
[0026] 1. The present invention uses Pickring emulsion as an adhesive to bond the chopped carbon fibers in the form of point-line contact. Compared with the traditional method of wrapping phenolic resin on the outside of the chopped carbon fibers, it has less influence on the conductivity of the three-dimensional network of carbon fibers, and has high conductivity without carbonizing the carbon paper.
[0027] 2. The present invention directly soaks the carbon fiber base paper in the Pickring emulsion, and applies a magnetic field to demulsify the emulsion to bond the carbon fiber. The method is simple and requires less dosage, saves costs, protects the environment, and avoids the problem of multiple impregnations with resin causing cracks in the carbon paper.
[0028] 3. Since carbon paper does not need to be carbonized or graphitized, it not only reduces energy consumption but also avoids the problem of reduced mechanical strength of carbon paper at high temperatures and has a higher porosity. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a flow chart for the preparation of ferroferric oxide / carbon nanotube composites;
[0030] Figure 2 is the particle size distribution diagram of Pickring nanoemulsion;
[0031] Figure 3 It is the Pickring nanoemulsion demulsification flow chart;
[0032] Figure 4 This is the SEM image of the homemade carbon paper;
[0033] Figure 5 This is the SEM image of Japan Toray carbon paper;
[0034] Figure 6 This is a comparison chart of the plane resistivity of different carbon papers. DETAILED DESCRIPTION
[0035] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0036] Example 1
[0037] Firstly, the carbon nanotubes were subjected to ultrasonic treatment at 60°C for 6 hours in a mixture of concentrated nitric acid and concentrated sulfuric acid in a mass ratio of 1:3 to oxidize the carbon nanotubes and introduce carboxyl groups on their surfaces to obtain carboxylated carbon nanotubes.
[0038] Secondly, if Figure 1 As shown, carbon nanotubes are ultrasonically dispersed in 50 ml of 1 mol / L FeSO4 solution and 50 ml of 1.75 mol / L FeCl3 solution and mixed, 1 mol / L sodium hydroxide solution is added dropwise to Ph=12, the temperature is raised to 50°C, heated for 3 h, and then 0.25 g of sodium dodecyl sulfate is added. After mixing evenly, the mixture is cooled to room temperature, and the black precipitate in the solution is collected by filtration, washed with deionized water until neutral, dried and ground to obtain a ferroferric oxide / carbon nanotube composite.
[0039] Then, 5 wt% of ferroferric oxide / carbon nanotube composite, 14.5 wt% of phenolic resin prepolymer, 0.5 wt% of n-hexane and 80 wt% of distilled water were stirred at 3000 rpm in a high-speed disperser for 30 min to prepare a Pickring emulsion adhesive. The particle size distribution diagram is shown in FIG. Figure 2 As shown;
[0040] The 9mm, 6mm and 3mm short-cut carbon fibers were mixed evenly with a small amount of PEM, PEO and distilled water respectively to prepare several 0.067wt% carbon fiber slurries; the carbon fiber base paper was made by a paper-making forming paper-making machine, and the carbon fiber base paper was put into the Pickring nanoemulsion, and the emulsion was demulsified by an alternating magnetic field, and the resin nanoparticles and the ferroferric oxide / carbon nanotube composite were precipitated and entered the fiber overlap point, such as Figure 3 As shown;
[0041] After freeze-drying the carbon paper base to remove water, it was hot-pressed at a temperature of 170°C, a pressure of 5 MPa, and a time of 60 minutes, and the orientation structure of the magnetic conductive particles was controlled by a magnetic field; during curing, on the one hand, the pressure caused the nano-adhesive to rupture, and the adhesive components were cured and bonded, and on the other hand, the conductive particles conducted the bonded carbon fibers to achieve the dual functionalization of bonding and conductivity to obtain a highly conductive fuel cell gas diffusion layer carbon paper. The SEM image of the homemade carbon paper is shown in the figure. Figure 4 shown.
[0042] The carbon paper prepared by this method is simple to prepare, uses less resin, has low cost, and has good conductivity of 12.11 mΩ·cm without carbonization or graphitization. Figure 6 As shown, the mechanical strength is high, which is 10.87MPa, and the thickness uniformity is good.
[0043] Example 2
[0044] Firstly, the carbon nanotubes were subjected to ultrasonic treatment at 60°C for 6 hours in a mixture of concentrated nitric acid and concentrated sulfuric acid in a mass ratio of 1:3 to oxidize the carbon nanotubes and introduce carboxyl groups on their surfaces to obtain carboxylated carbon nanotubes.
[0045] Secondly, a small amount of carboxylated carbon nanotubes was ultrasonically dispersed in 50 ml of 1 mol / L FeSO4 solution and 50 ml of 1.75 mol / L FeCl3, and then 1 mol / L sodium hydroxide solution was added dropwise to Ph=12, and the temperature was raised to 50°C and heated for 3 h, and then 0.25 g of sodium dodecyl sulfate was added, and the mixture was mixed and cooled to room temperature, and the black precipitate in the solution was collected by filtration, washed with deionized water until neutral, dried and ground to obtain a ferroferric oxide / carbon nanotube composite;
[0046] Then, 8 wt % of ferroferric oxide / carbon nanotube composite, 6 wt % of epoxy resin TDE-85, 2 wt % of polyetheramine and 84 wt % of distilled water were stirred at 3000 rpm in a high-speed disperser for 30 min to prepare a Pickring emulsion adhesive;
[0047] The 9mm, 6mm and 3mm short-cut carbon fibers are respectively mixed with a small amount of PEM, PEO and distilled water to prepare several 0.077wt% carbon fiber slurries; the carbon fiber base paper is then made by using a paper-making forming paper machine, and the carbon fiber base paper is placed in a Pickring nanoemulsion, and the emulsion is demulsified by using an alternating magnetic field, so that the resin nanoparticles and the ferroferric oxide / carbon nanotube composite are precipitated and enter the fiber overlap point;
[0048] The carbon paper base is freeze-dried to remove water, and then hot-pressed at a temperature of 90°C, a pressure of 5 MPa, and a time of 60 minutes, and the orientation structure of the magnetic conductive particles is controlled by a magnetic field; during curing, on the one hand, the pressure causes the nano-adhesive to rupture and the adhesive components to solidify and bond, and on the other hand, the conductive particles conduct the bonded carbon fibers to achieve dual functionalization of bonding and conductivity to obtain highly conductive fuel cell gas diffusion layer carbon paper.
[0049] The carbon paper prepared by this method is simple to prepare, uses less resin, has low cost, and has good conductivity of 12.01mΩ·cm without carbonization or graphitization, high mechanical strength of 11.29MPa, and good thickness uniformity.
[0050] Example 3
[0051] First, the carbon nanotubes were subjected to ultrasonic treatment for 6 hours in a mixture of concentrated nitric acid and concentrated sulfuric acid at a mass ratio of 1:3 at 60° C. to oxidize the carbon nanotubes and introduce carboxyl groups on their surfaces to obtain carboxylated carbon nanotubes.
[0052] Secondly, a small amount of carboxylated carbon nanotubes was ultrasonically dispersed in 50 ml of 1 mol / L FeSO4 solution and 50 ml of 1.75 mol / L FeCl3 solution and mixed, 1 mol / L sodium hydroxide solution was added dropwise to Ph=12, the temperature was raised to 50°C, heated for 3 h, and then 0.25 g of sodium dodecyl sulfate was added. After mixing evenly, the mixture was cooled to room temperature, and the black precipitate in the solution was collected by filtration, washed with deionized water until neutral, dried and ground to obtain a ferroferric oxide / carbon nanotube composite.
[0053] Then, 8 wt % of ferroferric oxide / carbon nanotube composite, 10 wt % of epoxy resin E51, 2.5 wt % of triethylenetetramine and 79.5 wt % of distilled water were stirred at 3000 rpm in a high-speed disperser for 30 min to prepare a Pickring emulsion adhesive;
[0054] The 9mm, 6mm and 3mm short-cut carbon fibers are respectively mixed evenly with a small amount of PEM, PEO and distilled water to prepare several 0.074wt% carbon fiber slurries; the carbon fiber base paper is then made by using a paper-making forming paper machine, and the carbon fiber base paper is placed in a Pickring nanoemulsion, and the emulsion is demulsified by using an alternating magnetic field, so that the resin nanoparticles and the ferroferric oxide / carbon nanotube composite are precipitated and enter the fiber overlap points;
[0055] The carbon paper base is freeze-dried to remove water, and then hot-pressed at a temperature of 100°C, a pressure of 5 MPa, and a time of 60 minutes, and the orientation structure of the magnetic conductive particles is controlled by a magnetic field; during curing, on the one hand, the pressure causes the nano-adhesive to rupture and the adhesive components to solidify and bond, and on the other hand, the conductive particles conduct the bonded carbon fibers to achieve dual functionalization of bonding and conductivity to obtain highly conductive fuel cell gas diffusion layer carbon paper.
[0056] The carbon paper prepared by this method is simple to prepare, uses less resin, has low cost, and has good conductivity of 13.73mΩ·cm without carbonization or graphitization, high mechanical strength of 10.34MPa, and good thickness uniformity.
[0057] Example 4
[0058] First, the carbon nanotubes were subjected to ultrasonic treatment for 6 hours in a mixture of concentrated nitric acid and concentrated sulfuric acid at a mass ratio of 1:3 at 60° C. to oxidize the carbon nanotubes and introduce carboxyl groups on their surfaces to obtain carboxylated carbon nanotubes.
[0059] Secondly, a small amount of carboxylated carbon nanotubes was ultrasonically dispersed in 50 ml of 1 mol / L FeSO4 solution and 50 ml of 1.75 mol / L FeCl3 solution and mixed, 1 mol / L sodium hydroxide solution was added dropwise to Ph=12, the temperature was raised to 50°C, heated for 3 h, and then 0.25 g of sodium dodecyl sulfate was added. After mixing evenly, the mixture was cooled to room temperature, and the black precipitate in the solution was collected by filtration, washed with deionized water until neutral, dried and ground to obtain a ferroferric oxide / carbon nanotube composite.
[0060] Then, 5 wt % of ferroferric oxide / carbon nanotube composite, 14.5 wt % of phenolic resin prepolymer, 0.5 wt % of cyclohexane and 80 wt % of distilled water were stirred at 3000 rpm in a high-speed disperser for 30 min to prepare a Pickring emulsion adhesive;
[0061] 9mm, 6mm, and 3mm asphalt-based carbon fibers are respectively mixed evenly with a small amount of PEM, PEO, and distilled water to prepare several 0.067wt% carbon fiber slurries; a papermaking forming paper machine is used to make paper to obtain carbon fiber base paper, and the carbon fiber base paper is placed in a Pickring nanoemulsion, and an alternating magnetic field is used to demulsify the emulsion, so that resin nanoparticles and ferroferric oxide / carbon nanotube composites are precipitated and enter the fiber overlap points;
[0062] The carbon paper base is freeze-dried to remove water, and then hot-pressed at a temperature of 170°C, a pressure of 5 MPa, and a time of 60 minutes, and the orientation structure of the magnetic conductive particles is controlled by a magnetic field; during curing, on the one hand, the pressure causes the nano-adhesive to rupture and the adhesive components to solidify and bond, and on the other hand, the conductive particles conduct the bonded carbon fibers to achieve dual functionalization of bonding and conductivity to obtain highly conductive fuel cell gas diffusion layer carbon paper.
[0063] The carbon paper prepared by this method is simple to prepare, uses less resin, has low cost, and has good conductivity of 19.27mΩ·cm without carbonization or graphitization, high mechanical strength of 9.89MPa, and good thickness uniformity.
[0064] Example 5
[0065] First, the carbon nanotubes were subjected to ultrasonic treatment for 6 hours in a mixture of concentrated nitric acid and concentrated sulfuric acid at a mass ratio of 1:3 at 60° C. to oxidize the carbon nanotubes and introduce carboxyl groups on their surfaces to obtain carboxylated carbon nanotubes.
[0066] Secondly, a small amount of carboxylated carbon nanotubes was ultrasonically dispersed in 50 ml of 1 mol / L FeSO4 solution and 50 ml of 1.75 mol / L FeCl3 solution and mixed, 1 mol / L sodium hydroxide solution was added dropwise to Ph=12, the temperature was raised to 50°C, heated for 3 h, and then 0.25 g of sodium dodecyl sulfate was added. After mixing evenly, the mixture was cooled to room temperature, and the black precipitate in the solution was collected by filtration, washed with deionized water until neutral, dried and ground to obtain a ferroferric oxide / carbon nanotube composite.
[0067] Then, 5 wt % of ferroferric oxide / carbon nanotube composite, 14.5 wt % of phenolic resin prepolymer, 0.5 wt % of cyclohexane and 80 wt % of distilled water were stirred at 3000 rpm in a high-speed disperser for 30 min to prepare a Pickring emulsion adhesive;
[0068] The 9mm, 6mm and 3mm short-cut carbon fibers are respectively mixed evenly with a small amount of PEM, PEO and distilled water to prepare several 0.067wt% carbon fiber slurries; the carbon fiber base paper is then made by using a paper-making forming paper machine, and the carbon fiber base paper is placed in a Pickring nanoemulsion, and the emulsion is demulsified by using an alternating magnetic field, so that the resin nanoparticles and the ferroferric oxide / carbon nanotube composite are precipitated and enter the fiber overlap point;
[0069] The carbon paper base is freeze-dried to remove water, and then hot-pressed at a temperature of 170°C, a pressure of 5 MPa, and a time of 60 minutes, and the orientation structure of the magnetic conductive particles is controlled by a magnetic field; during curing, on the one hand, the pressure causes the nano-adhesive to rupture and the adhesive components to solidify and bond, and on the other hand, the conductive particles conduct the bonded carbon fibers to achieve dual functionalization of bonding and conductivity to obtain highly conductive fuel cell gas diffusion layer carbon paper.
[0070] The carbon paper prepared by this method is simple to prepare, uses less resin, has low cost, and has good conductivity of 22.37mΩ·cm without carbonization or graphitization, and has high mechanical strength of 13.28MPa.
Claims
1. A method for preparing carbon paper for a fuel cell gas diffusion layer, characterized in that: The method is: (1) oxidizing carbon nanotubes under strong acid and ultrasonic conditions to obtain carboxylated carbon nanotubes; (2) mixing the carboxylated carbon nanotubes with a soluble salt solution containing divalent iron and trivalent iron, adding a small amount of sodium hydroxide solution, and preparing a ferroferric oxide / carbon nanotube composite by a coprecipitation method; (3) preparing a Pickring emulsion adhesive by mixing 5-20 wt % of a ferrosoferric oxide / carbon nanotube composite, 5-10 wt % of an adhesive, 0.5-2 wt % of a resin diluent and 70-85 wt % of distilled water; (4) dispersing carbon fiber in an aqueous solution containing a dispersant and a surfactant, preparing carbon fiber slurry by beating, and making paper with a papermaking forming paper machine to obtain carbon fiber base paper; wherein the dispersant is 0.10wt%-0.25wt%, the surfactant is 0.01-0.03wt%, the carbon fiber is 0.05-0.1wt%, and the distilled water is 99.62wt%-99.77wt%; (5) immersing the carbon fiber base paper in a Pickring emulsion adhesive, and in-situ demulsifying the emulsion particles by an alternating magnetic field, so that the adhesive / ferroferric oxide / carbon nanotube composite particles are precipitated and adsorbed at the fiber overlap points by capillary action, thereby obtaining a carbon fiber bonding base paper; (6) The carbon fiber bonding base paper is dehydrated, the magnetic field is used to control the orientation of the magnetic conductive particles, and the hot pressing is performed in sequence to obtain the carbon paper for the fuel cell gas diffusion layer.
2. The method for preparing carbon paper for a fuel cell gas diffusion layer according to claim 1, characterized in that: In step (1), the strong acid is one or more of concentrated sulfuric acid, concentrated hydrochloric acid or concentrated nitric acid, the oxidation temperature is 50-100° C., and the time is 3-8 h.
3. The method for preparing carbon paper for a fuel cell gas diffusion layer according to claim 1, characterized in that: In step (2), the divalent iron is ferrous sulfate or ferrous chloride, and the ferric iron is ferric nitrate or ferric chloride; the concentration ratio of the divalent iron to the ferric iron is 1:1.75, and the dosage ratio is 1:
1.
4. The method for preparing carbon paper for a fuel cell gas diffusion layer according to claim 1, characterized in that: In step (2), the heating temperature of the coprecipitation method is 30-80°C and the time is 2-6h.
5. The method for preparing carbon paper for a fuel cell gas diffusion layer according to claim 1, characterized in that: In step (3), the adhesive is one or more of phenolic resin, epoxy resin (TDE-85), epoxy resin (E51); the resin diluent is one of n-hexane, triethylenetetramine or polyetheramine.
6. The method for preparing carbon paper for a fuel cell gas diffusion layer according to claim 1, characterized in that: In step (4), the length of the carbon fiber is one or more of 1-9 mm; and the mass fraction of the carbon fiber in the carbon fiber slurry is 0.01 wt%-0.1 wt%.
7. The method for preparing carbon paper for a fuel cell gas diffusion layer according to claim 1, characterized in that: In step (4), the carbon fiber is one or more of polyacrylonitrile (PAN)-based carbon fiber or asphalt-based carbon fiber; the surfactant is one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate or Tween-80; the dispersant is one or more of polyethylene oxide (PEO), polyacrylamide (PAM), hydroxymethyl cellulose (CMC), and sodium hexametaphosphate.
8. The method for preparing carbon paper for a fuel cell gas diffusion layer according to claim 1, characterized in that: In step (6), the hot pressing treatment temperature is 80-180°C, the pressure is 2.5-10Mpa, and the time is 30-120min.
9. A carbon paper for a fuel cell gas diffusion layer prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing ferroferric oxide / carbon nano tube composite material
CN102583315A
Self-supporting flexible carbon nano-tube paper composite electrode material for lithium ion battery
CN102593436A
Method for largely loading Fe3O4 nanometer particles on carbon nanometer paper
CN103343477A
Carbon nanotube and nanofiber film-based membrane electrode assemblies
US20120301812A1
Cited By
Preparation method of ordered oriented short fiber molded carbon / carbon plate
CN121135455A
